2009
DOI: 10.1017/s1368980009005175
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fruit and vegetable intake in England: a re-examination based on quantile regression

Abstract: Objective: To examine the sociodemographic determinants of fruit and vegetable (F&V) consumption in England and determine the differential effects of socioeconomic variables at various parts of the intake distribution, with a special focus on severely inadequate intakes. Design: Quantile regression, expressing F&V intake as a function of sociodemographic variables, is employed. Here, quantile regression flexibly allows variables such as ethnicity to exert effects on F&V intake that vary depending on existing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
0
14
2
Order By: Relevance
“…In two studies [17,28], food intakes were compared between income groups and nutrient intakes were compared with reference values and between income groups. Diverse dietary assessment methods were used to estimate the food and/or nutrient intakes: a 24-h diet recall (24HDR) [11,13,29], food frequency questionnaire (FFQ) [11,12,14,15,19,21,22,23,24,25,30,31,32], diet record (DR) [16,17,20,25,26,28], food behavior surveys [18,28], and household food consumption survey [5] were employed, whereas an FFQ along with 24 HDR and 4 days of DR were used in two studies [11,25]. …”
Section: Resultsmentioning
confidence: 99%
“…In two studies [17,28], food intakes were compared between income groups and nutrient intakes were compared with reference values and between income groups. Diverse dietary assessment methods were used to estimate the food and/or nutrient intakes: a 24-h diet recall (24HDR) [11,13,29], food frequency questionnaire (FFQ) [11,12,14,15,19,21,22,23,24,25,30,31,32], diet record (DR) [16,17,20,25,26,28], food behavior surveys [18,28], and household food consumption survey [5] were employed, whereas an FFQ along with 24 HDR and 4 days of DR were used in two studies [11,25]. …”
Section: Resultsmentioning
confidence: 99%
“…The fact that having children does not increase household fruit and vegetable intake may be explained by the fact that children themselves were found to not consume adequate servings of fruits and vegetables [36]. According to Boukouvalas et al [37], as income increases, fruit and vegetable intake also increases, however, this effect tends to level off as income gets larger. Likewise, in this study, as household income level increases, so does mean daily fruit and vegetable intake with a mean intake of 6.86 daily reported by participants with household income greater than 966 USD.…”
Section: Discussionmentioning
confidence: 99%
“…Being a caregiver was found to affect fruit and vegetable intake significantly. As aging is associated with chronic diseases, caregivers may identify fruits and vegetables as being an important part of a healthy diet [37]. The marital status of the participants did not affect the fruit and vegetable intake.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5][6]8,9 This study aimed to examine these factors in King's County as compared to Glace Bay and determine whether there was a difference in food consumption patterns. Another study looking at socioeconomic status and its relation to household eating habits found that household size composition, education, and income combined explained only 21% to 29% of the variation in food purchasing.…”
Section: Discussionmentioning
confidence: 99%
“…Obtained education level influences the type of job and resulting income an individual can obtain as well as the awareness of healthy behaviors and eating practices. 7,8 Higher education as well as an increased income correlate with greater fruit and vegetable consumption, 1 whereas lower education tends to correlate with a higher occurrence of unhealthy behaviors such as increased smoking and fat consumption with lower levels of physical activity. 6 Stable employment with an adequate income is important to maintain household food security and balance other household expenses.…”
Section: Introductionmentioning
confidence: 99%